Optimization of Analgesia in the Emergence Period after the Surgical Correction of Scoliosis - N. G. Ilyina; S. M. Stepanenko; A. K. Shaginyan; Ye. V. Zilbert (Общая реаниматология, 2009)
The problem of postoperative analgesia has been attracting scrupulous attention for many years. The consequences of inadequate treatment for pain are highly significant in terms of physical or emotional injury. Objective: to optimize analgesia in the emergence period after the surgical correction of scoliosis. Subjects and methods. A total of 64 patients divided into groups by the mode of analgesia were examined. The parameters of hemodynamics, cardiointervalography, and the scores of pain, the therapy of which involved perfalgan at the final stage of anesthesia met the criteria for adequate analgesia. Results. Increased pain sensation was observed at the emergence stage in the group of patients where fentanyl administration was routinely stopped 30 minutes before the end of surgery. To prevent the intractable pain syndrome, therapy should be initiated at once when it occurs and preventive analgesia should be initiated in predictable pain (such as elective surgical intervention). The preemptive administration of perfalgan at the final stage of anesthesia with a controlled intravenous anesthetic (diprivan) prevented the development of intensive pain sensations after extubation, failed to prolong the emergence period, and made reversal of anesthesia and transportation of patients to a unit comfortable and less painful. Key words: analgesia, scoliosis, perfalgan.